Determining the level of awareness in wealth management / Nor Hazwani Mohd Sukaini - Mohd Sukaini, Nor Hazwani (Faculty of Business and Management, 2011)
The acknowledged widespread lack of awareness in wealth management casts serious doubts on the ability of individuals to make financial decisions. This investigation becomes imperative now that all efforts toward restructuring practically every sector of the economy for sustainable growth and development. The objective of this study is to identify the factors that most influence the level of awareness in wealth management. The factors are financial knowledge, gender, occupational status and age of the respondent. Therefore, this study has been developed with the aim to identify the most influential factor that influences the level of awareness in wealth management. The study was conducted through questionnaires with selected public at Am Assurance Headquarters. The data were analyed using SPSS Software. It was found that the most influential factor is financial knowledge of the respondents. Furthermore, age is also a very important factor that influences the level of awareness in wealth management.